A co-designed curriculum for cultural safety training of Colombian health professionals: sequential-consensual qualitative study (Canadian Medical Education Journal, 2022)
Background: Although traditional and cultural health practices are widely used in Colombia, physicians are not trained to address intercultural tensions that arise in clinical practice. Cultural safety encourages practitioners to examine how their own culture shapes their clinical practice and to respect their patients’ culture. It requires inviting patients of non-dominant cultures to co-design culturally safe health care. We co-designed a curriculum for cultural safety training of Colombian health professionals.Methods: A sequential-consensual qualitative study defined the learning objectives of the curriculum. Semi-structured questionnaires and focus groups explored the opinions of traditional medicine users, medical students, and intercultural health experts to inform the content of the curriculum. Deliberative dialogue between key intercultural health experts settled the academic content of the curriculum. A member-checking strategy modified and approved the final version.Results: Seven traditional medicine users, six medical students, and four intercultural health experts participated in the study. The stakeholders defined five learning objectives: (a) culturally unsafe practices: acknowledge the intercultural tensions and its consequences; (b) cultural awareness: examine their attitudes, beliefs, and values, and how they shape their professional practice; (c) cultural humility: listen and learn from the patients’ traditional practices; (d) cultural competence: describe current pedagogical approaches to address intercultural tensions; and (e) cultural safety: discuss with patients to reach an agreement on their treatment.Conclusion: This study integrated the perspectives of different stakeholders and proposed new applications of cultural safety that are relevant to other countries. Researchers and educators can use these results to inform future cultural safety initiatives.